TELAAH TENTANG HAK WARIS KERABAT NON-MUSLIM PERSPEKTIF MAQASHID SYARIAH AHMAD AR-RAISUNI - R. Fakhrurrazi; Faiz Zainuddin; Alicia Safira Azzuri (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
One of the discussions in inheritance law is about the causes of inheritance and its barriers. Things that can hinder inheritance include religious differences between heirs and heirs. The underlying proposition is the hadith of Osama ibn Zaid according to the narration of Bukhari Muslim. In this case there must be a fairly sharp analysis of the hadith because it cannot be denied that there are many kinship relationships that have different beliefs and there will be many benefits. Thus the formulation of the problem was born as follows: (1) What is the view of Islamic law regarding the giving and receiving of inheritance from non-Muslim relatives? and (2) What is the perspective of Ahmad ar-Raisuni's maqasid sharia regarding the giving and receiving of inheritance from non-Muslim relatives?. The purpose of this study is to describe the views of Islamic law regarding the giving and receiving of inheritance from non-Muslim relatives and to describe Ahmad ar-Raisuni's maqasid sharia perspective on the giving and receiving of inheritances from non-Muslim relatives. To answer the formulation of the problem, this study uses a type of library research (library research). The object of this research is Ahmad ar-Raisuni's maqasid sharia perspective on the giving and receiving of inheritance from non-Muslim relatives. Analysis of the data in this study used a descriptive method, namely describing and then analyzing the giving and receiving of inheritance from non-Muslim relatives from the perspective of Ahmad ar-Raisuni's sharia maqasid. The results of this study are: (1) The views of scholars regarding the giving and receiving of inheritance from non-Muslim relatives are divided into two. First, they only allow Muslims to receive inheritance from non-Muslim relatives. Second, they completely forbid either giving or receiving inheritance to non-Muslim relatives. (2) The issue of giving and receiving inheritance from non-Muslim relatives when it is associated with Ahmad ar-Raisuni's maqasid shari'a, will result in a law being allowed, taking into account the illat, arguments and benefits contained in the inheritance.